Oral cancer and tobacco: a case control study in southern India - C J, Nirmala; Thapsey, Hemanth; N. S., Murthy (International Journal Of Community Medicine And Public Health, 2017)
Background: Cancer is one of the major threats to public health in the developed world and increasingly in the developing world. In India, oral cancer is the leading cancer in males and ranking third in females. The risk factors for the development of oral cancers include tobacco smoking. Methods: A Case control study done at Kidwai Memorial Institute of Oncology, Bangalore, India. Study subjects included histological confirmed new cases of oral cancer attending the hospital during the period of April 2014- May 2015 and equal number of age and sex matched controls. Data collection was done by interview method. Results: Tobacco smoking with an odds ratio (OR) of 3.5 was significantly associated with the risk of oral cancer. The OR was 4.1 for combined bidi plus cigarette smokers and 3.7 for bidi smokers compared to non smokers. The OR was 2.3 for those who smoked less than or equal to 20 bidis/cigarettes per day and 8.3 for those who smoked more than 20 bidis/cigarettes per day, compared to non smokers. Smokers with pack years less than or equal to 20 showed 2.3 times, those with pack years 21- 29 showed 5.9 times and those with pack years more than 30 years showed 9.4 times higher risk for oral cancer compared to non smokers. Conclusions: Tobacco smoking shows higher risk for oral cancer. There is a great need to augment tobacco control measures and educate the public about harmful effects of tobacco consumption.